Pseudouridine synthase 1 promotes progression of hepatocellular carcinoma via mTOR and MYC signaling pathways - Chen, Li; Tan, Yonghuang; Li, Weinan; Huang, Lunkai; Li, Kang; Feng, Zanjie; Peng, Cijun; Mei, Yong (Frontiers in Oncology, 2025)
Pseudouridine synthases (PUSs) are associated with the development and progression of various cancers. However, the role of pseudouridine synthase 1 (PUS1) on HCC is unclear. The purpose of this study is to explore the biological role and mechanism of PUS1 in HCC growth and progression. We identified the expression of PUS1 in HCC. The biological roles and downstream cell signaling pathways of PUS1 were explored to clarify the molecular mechanism of PUS1 in the growth and development of HCC. The results showed that the expression of PUS1 was correlated with HCC progression, metastasis, and poor survival. In addition, the knockdown of PUS1 dramatically inhibited cell proliferation and colony formation and promoted cell apoptosis. GSEA analysis revealed that c-MYC, DNA repair, and mTORC1 pathways were significantly enriched in patients with high PUS1 expression. An intersection of the PUS1-dependent Ψ modification genes and c-MYC or mTORC1 pathway genes was performed. The expression of a part of these genes changed after PUS1 knockdown. Meanwhile, the expression of c-MYC and mTOR were down-regulated after PUS1 knockdown, but the inhibitory effect of PUS1 on cell growth capacity was not enhanced after inhibiting c-MYC or mTOR pathways. In conclusion, PUS1 regulates the occurrence and development of HCC through c-MYC and mTOR-related signaling pathways. It could be a novel molecule for clinical diagnosis, progression surveillance, prognosis assessment and therapeutic target of HCC.